The impact of periodic air pollution peaks in Beijing on air quality governance in China - Schwabe, Julian; Hassler, Markus (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
During the month of January 2013, Beijing suffered air pollution of unprecedented intensity. This event, which was named “airpocalypse” in international media, was followed by vibrant media reporting and public discussion on the topic and prompted the central government to issue unusually ambitious measures to contain air pollution more effectively. This paper explores the impact of the airpocalypse on China’s air quality governance by conducting a qualitative analysis of pollution control policies that followed the airpocalypse and concludes that this event of heavy air pollution was indeed impactful in causing the issuance of stricter national targets for pollution control as well as increased public awareness. In combination with the newly amended environmental protection law, these aspects put local governments under intense pressure to address air pollution more effectively. However, the changes caused by the airpocalypse were not revolutionary in a sense that it led to major structural reforms of government institutions and their interrelationships. The case of the airpocalypse demonstrates that single disruptive events of heavy pollution can cause a recalibration of policy priorities. In this context, the role of “disruptive events” may be worthwhile of more systematic research in order to understand their potential impact on institutional environments.